Patellar Instability in the Skeletally Immature - Popkin, Charles A. (Curr Rev Musculoskelet Med, 2018)
PURPOSE OF REVIEW: This review will focus on the evaluation and management of patellar instability in the developing patient. RECENT FINDINGS: A large number of surgical techniques have been described to prevent recurrent patellofemoral instability in the pediatric population, including both proximal and distal realignment procedures. The wide variety of treatment options highlights the lack of agreement as to the best surgical approach. However, when a comprehensive exam and workup are paired with a surgical plan to address each of the identified abnormalities, outcomes are predictably good. SUMMARY: Patellar instability is a common knee disorder in the skeletally immature patient that presents a unique set of challenges. Rates of re-dislocation in pediatric and adolescent patients are higher than in their adult counterparts. Careful consideration of the physeal and apophyseal anatomy is essential in these patients. While the majority of primary patellar instability events can be treated conservatively, multiple events often require surgical intervention.